Fellini, Dante and Paul: The Homo Viator and the Road to Conversion - Watt, Mary (Spunti e Ricerche, 2016)
In the closing moments of Federico Fellini’s La dolce vita, a young girl tries in vain to communicate with the film’s protagonist, Marcello. In the last moment of the shot, she turns to look directly at the camera as the film ends. Quite apart from the issue of what it is that the girl is trying to say, the enigmatic nature of the closing shot raises the even more fundamental question of what the director himself is trying to say.